Academic Writing Empowerment: Pendampingan Penulisan dan Publikasi Artikel Ilmiah bagi Dosen dan Tenaga Akademik - Moh. Wardi; Supandi Supandi; Heri Fadli Wahyudi; Ismail Ismail; Juhairiyah Juhairiyah; Siti Nur Aisyah; Siti Masriyah (Dharma: Jurnal Pengabdian Masyarakat, 2026)
Colleges play a strategic role in improving the quality of human resources through the implementation of the three pillars Colleges. However, many lecturers and academic staff still face challenges in writing and publishing scientific articles. This community service activity aims to enhance the capacity of educators in scientific work through training in scientific writing and publication using the Asset-Based Community Development (ABCD) approach for all educational staff. The ABCD approach encompasses the stages of discovery, dream, design, and destiny, allowing the impact of its success to be observed. The results of the activity demonstrate an improvement in participants’ understanding and skills in systematically drafting scientific articles, the strengthening of a productive academic culture, and an increase in the institution’s potential for scientific publication. This training makes a tangible contribution to strengthening the College’s academic reputation and competitiveness